Hospital dental care for a post-cerebral infarction patient - Nascimento, Paulo Pereira do; Patrocínio, Victor Hugo; Oliveira, Renata Lanzoni de; Paiva-Oliveira, Janayna Gomes; Gaetti-Jardim, Ellen Cristina (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Stroke presents as a deficiency of cerebral blood supply lowering the oxygen level and increasing the chance of irreversible tissue damage being such severity proportional to the extent and type of tissue injury, requiring immediate multiprofessional support. Thus, the objective is to present a clinical case of a 85-year-old female patient with stroke who underwent invasive dental treatment to eliminate the foci of infection and comfort to the patient concomitant to the hospitalization. Descriptors: Cerebral Infarction; Dental Care; Dental Service, Hospital; Ambulatory Care. Referências World Health Organization. (WHO). The top 10 causes of death. [Internet] Geneva; 2014. [Cited in 2016 Nov 22]. Available from: http://www.who. int/mediacentre/factsheets/fs310/em. Brasil. Ministério da saúde. Informações de saúde TABNET- Estatísticas vitais. Datasus. [internet]. [Citado em 2016 nov 22]. Disponível em: http://tabnet.datasus.gov.br Ghizoni JS, Taveira LAA, Garlet GP, Ghizoni MF, Pereira JR, Dionisio TJ et al. Increased levels of Porphyromonas gingivalis are associated with ischemic and hemorrhagic cerebrovascular disease in humans: an in vivo study. J Appl Oral Sci. 2012;20(1):104-12. Haraszthy VI, Zambon JJ, Trevisan M, Zeid M, Genco RJ. Identification of periodontal pathogens in atheromatous plaques. J Periodontol 2000; 71(10):1551-60. Seitz MW, Listl S, Bartols A, Schubert I, Blaschke K, Haux C et al. Current knowledge on correlations between highly prevalent dental conditions and chronic diseases: an umbrella review. Prev Chronic Dis. 2019;16:180641 Silva EJA. Reabilitação após o AVC [dissertação]. Porto: Faculdade de Medicina - Universidade de Porto; 2010. Patrocinio VH, Nascimento PP, Oliveira RL, Seco AJL, Fonseca RCL, Gaetti-Jardim EC. Extensa úlcera bucal em paciente com lúpus eritematoso. Rev Bras Ter Intensiva. 2019;31(2):266-68. Scannapieco FA, Genco RJ. Association of periodontal infections with atherosclerotic and pulmonary diseases. J Period Res. 1999;34(7):340-45. Noack B, Genco RJ, Trevisan M, Grossi S, Zambon JJ, De Nardin. E Periodontal Infections Contribute to Elevated Systemic C-Reactive Protein Level. J Periodontol. 2001;72(9):1221-27. Hashemipour MA, Afshar AJ, Borna R, Seddighi B, Motamedi A. Gingivitis and periodontitis as a risk factor for stroke: A case-control study in the Iranian population. Dent Res J (Isfahan). 2013;10(5):613-19.